Implementasi Hak Imunitas Ombudsman: Kajian terhadap Gugatan di Pengadilan Tata Usaha Negara - Mariyadi, Uswah; Moaht, Ortiz Saga (Justicia Insight, 2024)
The immunity rights of the Ombudsman represent a form of legal protection granted to this institution to maintain its independence and effectiveness in overseeing public services. However, the implementation of these immunity rights often becomes a point of contention when the Ombudsman faces lawsuits in the Administrative Court (PTUN). This study aims to analyze how the Ombudsman’s immunity rights are applied in handling lawsuits in the PTUN and to evaluate the extent to which existing legal provisions support or hinder their implementation. The research employs a normative juridical approach by examining legislation, court rulings, and relevant literature. The findings indicate that the Ombudsman’s immunity rights are explicitly regulated under Law Number 37 of 2008 concerning the Ombudsman of the Republic of Indonesia. However, in practice, misunderstandings frequently arise regarding the scope of this immunity, particularly in cases involving reports of maladministration submitted by the Ombudsman. The study concludes that the Ombudsman’s immunity rights need to be strengthened through outreach programs for law enforcement officials and the public, as well as through more comprehensive regulatory harmonization. This would enable the Ombudsman to perform its functions without interference while maintaining its accountability as a public institution.